Diversity of East China Summer Rainfall Change in Post-El Niño Summers - Zhang, Wen; Zhou, Xiaoye; Hsu, Pang-Chi; Liu, Fei (Frontiers in Earth Science, 2020)
East China has experienced positive precipitation anomalies in post-El Niño summers, mainly in the Yangtze-Huaihe River Valley. This kind of monsoonal rainfall change induced by El Niño, however, is not always the same due to El Niño diversity and mean state change. Here, we use cluster analysis on the post-El Niño (PE) East China summer precipitation anomalies to identify the diversity of this El Niño-induced monsoon change. The result shows that PE East China summer rainfall anomalies mainly display three different modes for all selected 20 El Niño events from 1957 to 2016. Cluster 1 shows the middle and lower reaches of the Yangtze River demonstrate strong wet anomalies, while South and North China are dominated by dry anomalies, similar to a sandwich mode. Cluster 2 is distinguished by dry anomalies over South China and wet anomalies over North China, exhibiting a dipole mode. Compared with Cluster 1, the change caused by Cluster 3 is different, showing negative anomalies over the Yangtze-Huaihe River Valley. The three clusters are correlated with successive events of El Niño, a quick transfer to a strong La Niña and a quick transfer to a weak La Niña respectively. The associated anomalous anticyclone (AAC) focuses on (120°E, 20°N) in Cluster 1, which expands southward for Cluster 2 and moves eastward for Cluster 3. The feedback of AAC-sea surface temperature (SST) mainly works for supporting the AAC in Cluster 1, but it is weak for Cluster 2; the strong easterly anomalies related to La Niña contribute to the AAC location change for Cluster 2. Both AAC-SST feedback and easterly anomalies support the AAC of Cluster 3. The CMIP5 output can capture these diverse responses in circulation except that their simulated AAC for Cluster 1 is significant to the east of the observed.